Real World Justice
VI, 408 p.
Keywords: The concept of global justice makes visible how we citizens of affluent countries are potentially implicated in the horrors so many must endure in the so-called less developed countries. Distinct conceptions of global justice differ in their specific criteria of global justice. However, they agree that the touchstone is how well our global institutional order is doing, compared to its feasible alternatives, in regard to the fundamental human interests that matter from a moral point of view. We are responsible for global regimes such as the global trading system and the rules governing military interventions. These institutional arrangements affect human beings worldwide, for instance by shaping the options and incentives of governments and corporations. Alternative paths of globalization would have differed in how much violence, oppression, and extreme poverty they engender. And global institutional reforms could greatly enhance human rights fullfillment in the future. The importance of this global justice approach reaches well beyond philosophy. It enables ordinary citizens to understand their options and responsibility for global institutional factors, and it challenges social scientists to address the causes of poverty and hunger that act across borders. The present volume addresses four main topics regarding global justice: The normative grounds for claims regarding the global institutional order, the substantive normative principles for a legitimate global order, the roles of legal human rights standards, and some institutional arrangements that may make the present world order less unjust. All royalties from this book have been assigned to Oxfam.